유구치와 제1대구치에서의 우상치 유병률과 유병률 간의 상관관계 - 우승희; Seunghee Woo; 김종수; Jongsoo Kim; 이준행; Joonhaeng Lee; 김종빈; Jongbin Kim (대한구강보건학회지, 2020)
Objectives: The purpose of this study was to investigate the prevalence of permanent first molar taurodontism and identify the correlation between primary molars and permanent first molar taurodontism. Methods: Among the 10,113 children who underwent panoramic radiography at a dental hospital from January 2010 to December 2019, 685 children (404 boys, 281 girls) were included in this study. Results: Six children (0.8%) and 98 children (14.1%) showed taurodontism of the primary molars and permanent first molar, respectively. All of the children with taurodontism in the primary molars had at least one taurodontism in the permanent first molars. Conclusions: Early diagnosis of taurodontism in primary molars might allow dentists to make treatment plans in accordance with tooth development.